Production and characterization of monoclonal anti-ovalbumin antibodies - Doymaz, Mehmet; Bulut, Tevfık Hakan; Özdarendeli, Aykut; Bolat, Yusuf (My University, 2000)
In this study, the results of anti-ovalbumin (OVA) monoclonal antibody production and characterization are reported. Splenocytes from OVA-hyperimmune Balb/C mouse were fused with F0 myeloma cells and resulting hybridoma cells were selected in hypoxanthine -aminopterine-thymidine containing medium. A total of 37 HAT resistant hybridomas were obtained. Upon testing the hybridoma supernatants in OVA and mouse immunoglobulin G specific enzyme-linked immunosorbent assays, we observed that two of the hybridomas secreted OVA specific antibodies. The hybridomas produced IgG class antibodies. The hybridomas were grown and the supernatants from the cultures were also tested in a Western Blot assay. The results of ELISA were confirmed with Western Blot assays. The results indicate that the mAbs produced in this study reacted with the continuous (non- conformational) epitopes present on OVA
Keywords: IgG; Antibodies; Monoclonal; Enzyme-Linked Immunosorbent Assay; Ovalbumin; Hybridomas